Groundwater Quality Assessment from a Hydrogeochemical Viewpoint A Case Study of Sarab County - Mojtaba Pourakbar (آب و فاضلاب, 2015)
Groundwater resources are the most important sources of drinking water in many communities. The direct impact of water quality on public health warrants a thorough investigation of water quality and the factors involved from a hydrogeochemical viewpoint. In the present study, 25 villages of Sarab County in East Azerbayejan Province were selected and the quality of the drinking water supplied in the region was analyzed in terms of its physicochemical parameters along with heavy metals content including 20 different metals. The results were plotted using the Arc GIS for interpretation. The selected villages were subsequently categorized using the Principal Component Analysis (PCA) and the Hierarchical Cluster Analysis. Based on the result of study, the EC of the drinking water ranged over 220-2990µs/cm with an average value of 812.  A remarkable finding was the high level of dissolved solids in the Western parts of the study area. Arsenic in two villages and mercury in one village were also high. PCA results showed that the drinking water in the pilot villages could be divided into three categories. Based on certain water quality problems observed ij the region, it is suggested that substitute water supplies should be identified for some of the villages while a comprehensive investigation is also carried out on the arsenic anomaly and its health effects on water consumers in the contaminated villages.